2019
DOI: 10.7824/rbh.v18i1.636
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de herbicidas na cultura do cártamo

Abstract: O cártamo (Carthamus tinctorius L.) é uma planta oleaginosa que apresenta elevado potencial de cultivo no Brasil. O controle das plantas daninhas na cultura é essencial para proteger o seu potencial produtivo. O objetivo deste estudo foi avaliar a seletividade de herbicidas aplicados em pré-plantio incorporado (PPI), pré-plantio (PRÉ) e pós-emergência (PÓS) do cártamo. Ao todo, três estudos foram instalados em casa de vegetação, em delineamento inteiramente casualizado, com cinco repetições. Os herbicidas aval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In the same way, propyzamide caused low safflower injury (1, in a scale of 1-9) but poor weed control, ranged from 46% to 78% efficacy, and had grain yield losses due to the competition of uncontrolled weeds [12]. On the other hand, metazachlor and metribuzin, independently to their efficacy on weeds, caused high phytotoxic effects on the safflower, and so they seemed to be not advisable to use as pre-emergence herbicides for weed control in this crop, as observed also by Krenchinski et al [19] and Montemurro and Fracchiolla [12]. These two latter authors found that metribuzin, in a location of south Italy, gave a high safflower phytotoxicity (7, in a scale of 1-9), an efficacy of 61% against a weed infestation of Avena ludoviciana Durieu (23% of ground cover), Galium aparine L. (8% of ground cover), and Sinapis arvensis L (5% of ground cover), and the lowest grain yield (1.18 t ha −1 ) [12].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In the same way, propyzamide caused low safflower injury (1, in a scale of 1-9) but poor weed control, ranged from 46% to 78% efficacy, and had grain yield losses due to the competition of uncontrolled weeds [12]. On the other hand, metazachlor and metribuzin, independently to their efficacy on weeds, caused high phytotoxic effects on the safflower, and so they seemed to be not advisable to use as pre-emergence herbicides for weed control in this crop, as observed also by Krenchinski et al [19] and Montemurro and Fracchiolla [12]. These two latter authors found that metribuzin, in a location of south Italy, gave a high safflower phytotoxicity (7, in a scale of 1-9), an efficacy of 61% against a weed infestation of Avena ludoviciana Durieu (23% of ground cover), Galium aparine L. (8% of ground cover), and Sinapis arvensis L (5% of ground cover), and the lowest grain yield (1.18 t ha −1 ) [12].…”
Section: Discussionmentioning
confidence: 91%
“…These two latter authors found that metribuzin, in a location of south Italy, gave a high safflower phytotoxicity (7, in a scale of 1-9), an efficacy of 61% against a weed infestation of Avena ludoviciana Durieu (23% of ground cover), Galium aparine L. (8% of ground cover), and Sinapis arvensis L (5% of ground cover), and the lowest grain yield (1.18 t ha −1 ) [12]. Krenchinski et al [19] reported that metribuzin, at 360 g a.i. ha −1 , had injured safflower more when applied in pre-emergence (96% of phytotoxicity at 4 weeks after treatment) than when used pre-planting incorporated (41% of phytotoxicity).…”
Section: Discussionmentioning
confidence: 99%